A re-appraisal of the widely-distributed freshwater crab genus Sinopotamon Bott, 1967, from China, with establishment of a new genus (Crustacea: Decapoda: Potamidae) - Shih, Hsi-Te; Huang, Chao; Ng, Peter K. L. (Zootaxa, 2016)
Freshwater crabs of the genus Sinopotamon Bott, 1967 (family Potamidae) are widely distributed along the Yangtze River (= Chang Jiang) drainage and are endemic to China. Two distinct clades can be distinguished within Sinopotamon s. lato. on the basis of morphological and molecular data. One clade corresponds to Sinopotamon s. str., with the type species Potamon (Potamon) davidi Rathbun, 1904, and 11 other species, all which occur in the Sichuan Basin (including Sichuan Province and Chongqing City) and reach the border areas of adjacent Shaanxi, Hubei, and Guizhou provinces. A new genus, Longpotamon gen. nov., is proposed for the second clade, with Sinopotamon exiguum Dai, 1997, designated as the type species. Sinopotamon s. str. can be distinguished from Longpotamon gen. nov. by the shape of the male telson and by characters of the male first gonopod and the female vulvae. These differences are supported by the mitochondrial 16S rDNA and cytochrome oxidase subunit I (COI) genetic data. Longpotamon gen. nov. is the largest clade, with 73 known species and a wide distribution along the Yangtze River drainage extending north to the Yellow River drainage and south to the eastern side of Wuyishan Range. The two genera overlap in the Sichuan Basin and the adjacent provinces.